Unveiling large-scale velocity characteristics of rock glaciers in the Tibet-Pamir-Karakoram region using InSAR - Zhangyu Sun; Lin Liu; Chengyan Fan; Yan Hu; Francesca Baldacchino; Atanu Bhattacharya; Ella Wood; Tobias Bolch (International Journal of Applied Earth Observations and Geoinformation)
Rock glaciers are debris landforms formed by long-term creep of ice-rich permafrost. Their kinematics provide critical insights for climate change and permafrost studies, mountain hydrology, and hazard assessment. Previous studies have measured rock glacier velocities using field-based terrestrial geodetic surveys, repeat photogrammetry, and Interferometric Synthetic Aperture Radar (InSAR). However, these methods have typically been confined to local regions, leaving the large-scale velocity characteristics underexplored. In this study, we developed a multi-temporal and multi-geometry InSAR framework for systematically generating rock glacier velocity fields. We rigorously validated our approach by comparing the InSAR-derived velocities with those derived from very-high-resolution optical imagery (Pléiades satellite imagery and aerial imagery) and Global Navigation Satellite System (GNSS) measurements. The mean relative difference is approximately 20 % when compared to velocities from Pléiades and aerial images, increasing to 50 % for GNSS point measurements. Applying our method, we produced the first large-scale regional rock glacier velocity dataset, encompassing downslope velocity fields for 19,727 previously inventoried rock glaciers in the Tibet-Pamir-Karakoram region. We found a velocity contrast between different climatic domains: rock glaciers in the westerlies domain move on average faster (median = 30 cm/yr) than those in the monsoon domain (median = 13 cm/yr). Our study presents a methodological framework for assessing rock glacier velocities using InSAR and demonstrates its capability for large-scale applications. This approach can be readily adapted to other regions worldwide to support the assessment and monitoring of rock glacier dynamics in a changing climate.